Process and uses of alternative carbohydrate sources in pet foods and treats - Guazzelli Pezzali, Julia (Kansas State University, 2019)
The pet food industry has been rapidly growing for years. This growth has been driven by new product development which emphasized new ingredients and food forms. Starch sources are prominent ingredients in both complete & balance diets, and in snacks & treats. The overall objective of this project was to evaluate the performance of uncommon starch sources in dry expanded pet food, and in a novel dog treat. First, two dry expanded dog diets were formulated containing different types of starches: an ancient grain (AG; including spelt, millet and sorghum), and a grain-free diet (GF, including peas, potatoes, and tapioca starch). Experimental diets were evaluated for their impact on the extrusion process and nutrient utilization by dogs. A greater specific mechanical energy (141 vs. 117 kJ/kg) and in-barrel moisture (38.2 vs. 30.3 %) input were observed for GF compared to AG. The GF kibbles were more expanded (3.5 vs. 3) and harder (6.36 vs. 3.12 kg) than the AG. Apparent total tract digestibility of most nutrients was similar between AG and GF with exception of total dietary fiber which was 32% greater for dogs fed GF (P<0.05). Second, we evaluated the use of white and red sorghum flour (WSF and RSF, respectively) as potential ingredients for production of extruded crisps. Nutritional analysis revealed a higher protein (9.95 vs. 8.22 %) and a lower starch content (83.81 vs. 88.15 %) for WSF compared to RSF. Pasting properties were similar between WSF and RSF (P>0.05), but RSF exhibited higher initial (66.56 vs. 63.34 °C) and peak gelatinization (73.89 vs. 72.42 °C) temperatures. However, these differences did not influence the extrusion process. The WSF and RSF were extruded under similar processing parameters which resulted in expanded crisps with similar characteristics (P>0.05). Last, the use of sorghum crisps and soluble animal protein binders were evaluated for their effect on a cereal bar application for dogs. The experiment was conducted as a 3 x 5 factorial arrangement of treatments with three sources of crisp (rice crisp, RC; white sorghum crisp, WSC; and red sorghum crisp, RSC) and five sources of binder (corn syrup, CS; spray dried plasma, SDP; gelatin, GL; albumin, AL; and egg product, EP). Texture properties of each dietary treatment were evaluated, and dog’s preferences were assessed by a preference ranking test. Regarding textural properties, a significant binder by crisp source interaction was observed (P<0.05); wherein, the cereal bar produced with CS and RC presented the highest toughness. Cereal bars were well accepted by dogs and WSC cereal bars produced with SDP were preferred over those produced with EP (P<0.05). These studies demonstrate that starch sources may behave differently during extrusion processing, and can impact nutrient utilization and dog preference in complete & balanced diets, and in snacks & treats application. Characterization of raw materials and processing are essential to the development of new products that optimize both animal nutrition and processing conditions.
Keywords: Pet food; Pet treat; Grain-free; Ancient grains; Sorghum; Extrusion